2016
DOI: 10.1039/c4dt02929a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of riboflavin on the reduction of radionuclides by Shewanella oneidenis MR-1

Abstract: Uranium (as UO2(2+)), technetium (as TcO4(-)) and neptunium (as NpO2(+)) are highly mobile radionuclides that can be reduced enzymatically by a range of anaerobic and facultatively anaerobic microorganisms, including Shewanella oneidensis MR-1, to poorly soluble species. The redox chemistry of Pu is more complicated, but the dominant oxidation state in most environments is highly insoluble Pu(IV), which can be reduced to Pu(III) which has a potentially increased solubility which could enhance migration of Pu i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
(69 reference statements)
4
20
0
Order By: Relevance
“…In addition, there is one report which studied the effect of the addition of riboflavin in the microbial reduction of uranium (U), technetium (Tc), neptunium (Np) and plutonium (Pu) with S. oneidenis MR-1. 28 As was reported, the addition of 10 mol L -1 of riboflavin, enhanced the rate of microbial reduction of Tc(VII) to Tc(IV), Pu(VI) to Pu(III) and Np(V) to Np(IV) to a lesser extent, but riboflavin did not have any impact on the reduction of U(VI) to U(IV). Interestingly, the range of redox mediator concentrations in all three cases is very similar 160-16 mol L -1 in the case of Te(VI) and Te(IV), 130-13 mol L -1 in the case of Pt(IV) and 10 mol L -1 in the cases of Tc(VII), Pu(VI) and Np(V).…”
Section: Impact Of Redox Mediators In the Reduction Of Pt(iv)supporting
confidence: 51%
See 1 more Smart Citation
“…In addition, there is one report which studied the effect of the addition of riboflavin in the microbial reduction of uranium (U), technetium (Tc), neptunium (Np) and plutonium (Pu) with S. oneidenis MR-1. 28 As was reported, the addition of 10 mol L -1 of riboflavin, enhanced the rate of microbial reduction of Tc(VII) to Tc(IV), Pu(VI) to Pu(III) and Np(V) to Np(IV) to a lesser extent, but riboflavin did not have any impact on the reduction of U(VI) to U(IV). Interestingly, the range of redox mediator concentrations in all three cases is very similar 160-16 mol L -1 in the case of Te(VI) and Te(IV), 130-13 mol L -1 in the case of Pt(IV) and 10 mol L -1 in the cases of Tc(VII), Pu(VI) and Np(V).…”
Section: Impact Of Redox Mediators In the Reduction Of Pt(iv)supporting
confidence: 51%
“…In that research, lawsone and riboflavin were found capable of increasing the rate of the microbial reduction of Te(VI) and Te(IV), being lawsone the most effective for the reduction of Te(VI) and riboflavin the most effective for the reduction of Te(IV). In addition, there is one report which studied the effect of the addition of riboflavin in the microbial reduction of uranium (U), technetium (Tc), neptunium (Np) and plutonium (Pu) with S. oneidenis MR-1 28 . As it was reported, the addition of 10 µM of riboflavin, enhanced the rate of the microbial reduction of Tc(VII) to Tc(IV), Pu(VI) to Pu(III) and Np(V) to Np(IV) to a lesser extent, but riboflavin did not have any impact on the reduction of U(VI) to U(IV).…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms are associated with a variety of radioactive materials at U.S. Department of Energy contaminated sites (14,15), and it is apparent that Pu speciation and solubility can be affected by microbial activity (16)(17)(18)(19)(20)(21). Previous studies of Pseudomonas stutzeri and Bacillus sphaericus reported a sorption affinity of nearly 100 g Pu/g dry cell weight for Pu(VI) to the surface of vegetative cells and spores (20).…”
mentioning
confidence: 99%
“…At circumneutral pH in pure culture experiments, microbial reduction to Tc­(IV) can be coupled to electron donor (hydrogen and in some cases organic matter) oxidation via enzymatic pathways. , More widely, TcO 4 – reduction in many environmental systems seems to be dominated by redox reactions with Fe­(II)-bearing minerals, such as magnetite (Fe 2 O 3 ), , sorbed Fe­(II), which can be formed as a result of microbial Fe­(III) reduction, or pyrite (FeS 2 ) formed after reaction of Fe­(II) with sulfide, and again linked to microbial metabolism. At circumneutral pH, the rate of TcO 4 – reduction is influenced by Fe­(II) speciation and concentration, and potentially, the presence of redox shuttles. , When TcO 4 – is reduced in systems containing Fe­(II), X-ray absorption spectroscopy has shown that Tc forms poorly soluble hydrous TcO 2 -like phases (monomers–polymers), potentially with Fe associations. ,,, Incorporation of Tc­(IV) into Fe­(II)-bearing mineral phases has also been reported. Additionally, at ultradilute concentrations, where direct XAS speciation analysis is not possible (<10 –11 mol L –1 , below the solubility threshold for TcO 2 precipitation), Tc (as 99m Tc) has been shown to be retained on solids under reducing conditions, presumably as Tc­(IV) sorbed to geomaterials. Interestingly, Tc­(IV) solubility may increase at elevated salinity as well as when organics and carbonates are present at enhanced concentrations, and Tc has also been shown to be associated with Fe-bearing colloids. ,,,− However, the effect of changing biogeochemistry under alkaline conditions, on the reduction of Tc­(VII) remains poorly constrained.…”
Section: Introductionmentioning
confidence: 99%